Knowledge of Student Study Service on Caricaceae in Their Neighborhoods - Ainun Nikmati Laily; Purnomo; Budi Setiadi Daryono; Aziz Purwantoro (Nusantara Science and Technology Proceedings)
Indonesia is one of the countries with abundant and diverse natural resources so that it is known as mega biodiversity. The high biodiversity in Indonesia is partly due to its geographic location as a tropical country. Meanwhile, plants belonging to the Caricaceae are one of the groups of plants that are very easy to find, affordable prices, and can be grown in most areas in Indonesia. During the coronavirus (COVID-19) pandemic, the student study service from home (Indonesian: Kuliah Kerja Nyata – Virtual Dari Rumah - or KKN-VDR) requires college students to explore the potential of their place of residence, so knowledge about Caricaceae needs to be explored and studied to find out its potential use. This study aims to determine college students' knowledge of Caricaceae around where they live. This study uses a survey method. The results showed that the knowledge of student study service on the Caricaceae in several aspects had not yet reached what was desired. Thus it is necessary to conduct a joint evaluation to encourage the Indonesian student to be more critical in recognizing the potential of natural resources so that they can make the best use of them for welfare, especially Caricaceae.